2018
DOI: 10.1002/acm2.12314
|View full text |Cite
|
Sign up to set email alerts
|

Film‐based dose validation of Monte Carlo algorithm for Cyberknife system with a CIRS thorax phantom

Abstract: Monte Carlo (MC) simulation, as the most accurate dose calculation algorithm, is available in the MultiPlan treatment planning system for Cyberknife. The main purpose of this work was to perform experiments to thoroughly investigate the accuracy of the MC dose calculation algorithm. Besides the basic MC beam commissioning, two test scenarios were designed. First, single beam tests were performed with a solid water phantom to verify the MC source model in simple geometry. Then, a lung treatment plan on a CIRS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The Ray‐tracing algorithm calculates doses using only density correction of the primary photon components obtained from measured data such as OCR, TPR, and OPF. This calculation method does not consider the contribution of the scattered radiation component along the off‐axis direction . In contrast, the FSPB algorithm considers this in the calculation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Ray‐tracing algorithm calculates doses using only density correction of the primary photon components obtained from measured data such as OCR, TPR, and OPF. This calculation method does not consider the contribution of the scattered radiation component along the off‐axis direction . In contrast, the FSPB algorithm considers this in the calculation.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Pan et al reported that the dose errors at the center of the tumor in the lung-equivalent tissue were 0.68% and 13.37% for the MC and Ray-tracing algorithms in MultiPlan TPS with fixed collimators. 30 The Ray-tracing algorithm calculates doses using only density correction of the primary photon components obtained from measured data such as OCR, TPR, and OPF. This calculation method does not consider the contribution of the scattered radiation component along the off-axis direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motion tracking mode includes the Xsight lung tracking system and Synchrony Respiratory Tracking System. CIRS-Xsight lung tracking phantom kit is used in motion tracking system [9]. There are two orthogonal Radiochromic films loaded in phantoms.…”
Section: C1 End-to-end Testmentioning
confidence: 99%